2011
DOI: 10.1039/c0cp01595d
|View full text |Cite
|
Sign up to set email alerts
|

Application of London-type dispersion corrections to the solid-state density functional theory simulation of the terahertz spectra of crystalline pharmaceuticals

Abstract: The effects of applying an empirical dispersion correction to solid-state density functional theory methods were evaluated in the simulation of the crystal structure and low-frequency (10 to 90 cm(-1)) terahertz spectrum of the non-steroidal anti-inflammatory drug, naproxen. The naproxen molecular crystal is bound largely by weak London force interactions, as well as by more prominent interactions such as hydrogen bonding, and thus serves as a good model for the assessment of the pair-wise dispersion correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 37 publications
3
104
0
Order By: Relevance
“…7.11 Naproxen simulated spectrum with optimised dispersion parameters (A) compared with low temperature terahertz measurement. From [63]. Reproduced by permission of the PCCP Owner Societies the experimental low temperature unit cell parameters and excellent agreement with the experimental spectrum (see Fig.…”
Section: Density Functional Theory Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…7.11 Naproxen simulated spectrum with optimised dispersion parameters (A) compared with low temperature terahertz measurement. From [63]. Reproduced by permission of the PCCP Owner Societies the experimental low temperature unit cell parameters and excellent agreement with the experimental spectrum (see Fig.…”
Section: Density Functional Theory Resultssupporting
confidence: 58%
“…It is to be noticed that the choice of the dispersion correction parameters is not unique and can have a dramatic effect on the final results. For example, King [63] performed a series of calculations on naproxen (see Fig. 7.8) showing that, for this system, the dispersion correction implemented in the CRYSTAL09 code [36] generates a 10 % contraction in the unit cell when used with the PBE functional, an error which is almost equal in magnitude to the uncorrected PBE calculation, which results in +12 % volume expansion.…”
Section: Density Functional Theory Resultsmentioning
confidence: 99%
“…King and coworkers highlighted the advantages of the DFT-D techniques in studies of (i) 1-methylthymine, 9-methyladenine, and their 1:1 cocrystal 231 and (ii) the pharmaceutical naproxen. 232 In the former study, the strength and positions of the vibrational features matched the observed terahertz features much more closely when the DFT-D technique was employed, in particular for the cocrystal, which initially had produced unfeasible imaginary frequencies for the non-DFT-D technique, indicative of a non-energy-minimum conformation in the calculation. The second study highlighted one major issue with these parameterized techniques-the choice of coupling strength.…”
mentioning
confidence: 91%
“…Changes in crystal structure can alter the way in which the drug is absorbed and accessed by the body [11]. The chemical and molecular structure of a drug profoundly affects the stability, ease of manufacture and its biopharmaceutical performance.…”
Section: Introductionmentioning
confidence: 99%